2009
DOI: 10.1111/j.1525-1446.2009.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Events, Chronic Stressors, and Depressive Symptoms in Low‐Income Urban Mothers With Asthmatic Children

Abstract: Objective The purpose of this secondary data analysis was to examine the relationship of individual sociodemographic variables, life events, chronic stressors including asthma control and management and environmental stressors to maternal depression. Design Cross sectional descriptive design study consisting of baseline data from participants enrolled in a randomized clinical trial of an asthma communication educational intervention. Sample Two hundred and one mothers of children with asthma (ages 6-12) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 45 publications
5
25
2
Order By: Relevance
“…A greater proportion of mothers of adolescents with asthma had psychological distress compared to control mothers; however, the prevalence was lower than previously reported findings which have suggested that at least a quarter, and up to half of mothers of children with asthma have depression [30,31]. This discrepancy may be attributable to sampling.…”
Section: Discussioncontrasting
confidence: 81%
“…A greater proportion of mothers of adolescents with asthma had psychological distress compared to control mothers; however, the prevalence was lower than previously reported findings which have suggested that at least a quarter, and up to half of mothers of children with asthma have depression [30,31]. This discrepancy may be attributable to sampling.…”
Section: Discussioncontrasting
confidence: 81%
“…Furthermore, this study showed that among mothers with elevated depressive symptoms at 5 months, maternal reports of childhood asthma attacks were not statistically significantly associated with elevated depressive symptoms at 17 months postpartum, although a nonsignificant tendency toward increased odds of elevated depressive symptoms was observed with wide confidence intervals. Some studies have shown a greater prevalence of depressive symptoms among parents of asthmatic children (Kub et al, 2009) and among those who visit an emergency room for child asthma attacks (Bartlett et al, 2001). In contrast, other studies have shown the absence of an association between child asthma and maternal depressive symptoms, although the severity of the child's asthma seems to be associated with maternal depressive symptoms (Klinnert et al, 2001;Shalowitz et al, 2006).…”
Section: Discussionmentioning
confidence: 94%
“…Yet, few studies have examined the association between child asthma and maternal depressive symptoms (Akcakaya et al, 2003) and even the direction remains elusive (Gustafsson, Kjellman, & Bjorksten, 2002). Studies have either shown a positive association (Kub et al, 2009), or did not find any significant association in a sample of low income mothers (Shalowitz et al, 2006). Other research focused more extensively on the impact of child asthma on parents' quality of life (Levy et al, 2004;Williams et al, 2000;Ozkaya et al, 2010;Wright, 2011) or on the impact of maternal depression on child asthma morbidity and use of health care services (Bartlett et al, 2001;Klinnert et al, 2001).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations